Analysis of Demand Potential and Need for Passenger Terminal Facilities at Cikembar Sukabumi Airport - Setiawan, Agung; Akbardin, Juang; Maknun, Johar (Universitas Pendidikan Indonesia, 2021)
Abstract - West Java Province has a very unique and strategic geographic field challenge as a province with the largest population in Indonesia and as a province that is at the forefront of supporting the rapid dynamics of development in the capital city DKI Jakarta. In realizing equitable development, as stated in the West Java Provincial Medium-Term Development Plan (RPJMD) 2018-2023, infrastructure development is regulated in a priority scheme that aims to bring equitable development. One of the planned transportation infrastructure developments in the construction of Cikembar Airport, Sukabumi, is prepared to serve the development area (WP) of the Sukabumi area and its surroundings which is targeted for completion in 2023. In preparing the airport design, a projection analysis based on demand is needed first. which correlates with statistical data. Forecasting analysis (forecasting) the number of passengers at Cikembar Airport aims to obtain potential passenger demand and a description of the needs for terminal facilities through the collection of statistical data to be analyzed using the correlation method and the multiple linear regression method between the number of passengers as the dependent variable. Meanwhile, statistical variables such as population growth, tourist growth, and Gross Regional Domestic Product (GRDP), Sukabumi, and West Java Regencies were determined as independent variables. In formulating the terminal room facilities, it refers to the standards issued by the Directorate General of Civil Aviation through SKEP No.77/VI Year 2005. Considering the moderate upward trend approach, the estimated number of passengers at Cikembar Airport passenger terminal in 2023, namely the year the airport is planned to be realized, is as much as 756,029 passengers with busy time passengers totaling 605 passengers. The operational area needed for the terminal in that year was 8,468 m2. Assuming the concession area provided is 30%, the total terminal area required is 11,643 m2. This area projection still meets the needs based on the estimated terminal area attached to the Cikembar Airport master plan, which is 12,000 m2.